Th22 is the effector cell of thymosin β15-induced hair regeneration in mice - Nana Tao; Yuyuan Ying; Xie Xu; Qingru Sun; Yaoying Shu; Shiyu Hu; Zhaohuan Lou; Jianli Gao (BMC, 2024)
Abstract Background Thymosin beta family has a significant role in promoting hair regeneration, but which type of T cells play a key role in this process has not been deeply studied. This research aimed to find out the subtypes of T cell that play key role in hair regeneration mediated by thymosin beta 15 (Tβ15). Methods Ready-to-use adenovirus expressing mouse Tmsb15b (thymosin beta 15 overexpression, Tβ15 OX) and lentivirus-Tβ15 short hairpin RNA (Tβ15 sh) were used to evaluate the role of Tβ15 in hair regeneration and development. The effect of Th22 cells on hair regeneration was further studied by optimized Th22-skewing condition medium and IL-22 binding protein (IL-22BP, an endogenous antagonist of IL-22, also known as IL-22RA2) in both ex vivo culture C57BL/6J mouse skin and BALB/c nude mice transplanted with thymus organoid model. Results The results show that Tβ15, the homologous of Tβ4, can promote hair regeneration by increasing the proliferation activity of hair follicle cells. In addition, high-level expression of Tβ15 can not only increase the number of Th22 cells around hair follicles but also accelerate the transformation of hair follicles to maturity. Consistent with the expected results, when the IL-22BP inhibitor was used to interfere with Th22, the process of hair regeneration was blocked. Conclusions In conclusion, Th22 is the key effector cell of Tβ15 inducing hair regeneration. Both Tβ15 and Th22 may be the potential drug targets for hair regeneration.